Analisis Dinamika Hubungan Pemerintah Pusat dan Daerah Dalam Penanggulangan Pandemi Covid-19 di Indonesia - Muhammad Rizky Mubaroq; Lukmanul Hakim; Rahman Rahman (Universitas Medan Area, 2023)
The condition of the Corona Virus Disease 2019 or COVID-19 pandemic, which has been increasingly endemic in Indonesia since 2020, has resulted in a problem of authority between the Central Government and the Regional Government. The purpose of this study is to find out the relationship between the Central and Regional Governments in tackling the Covid-19 Pandemic in Indonesia. This study uses a qualitative approach. Literature studies are used to analyze the relationship between the center and regions in handling the COVID-19 pandemic. This approach involves a conceptual process and generates identification in understanding the problem. The results of the study show that the COVID-19 pandemic has affected every dimension of life, including central and regional relations in the corridors of decentralization in Indonesia. The government's efforts to deal with the pandemic and its impact on the socio-economic community have led to initiatives from the regional government. On the other hand, this initiative raises problems in the governance of central and regional relations. The central government must strengthen coordination with regional governments to deal with COVID-19. On the other hand, regional governments also need to be given the freedom to innovate in handling COVID-19, which cannot be predicted when it will end, provided that they do not have to overstep the authority of the central government and violate existing laws and regulations. Thus, it is hoped that Indonesia can jointly overcome the COVID-19 outbreak well, both at the central and regional levels in a synergistic manner.